Gut bacteria differentially affect egg production in the anautogenous mosquito Aedes aegypti and facultatively autogenous mosquito Aedes atropalpus (Diptera: Culicidae). Issue 1 (December 2016) - Coon, Kerri; Brown, Mark; Strand, Michael
Abstract Background Aedes aegypti andA. atropalpus are related mosquitoes that differ reproductively.Aedes aegypti must blood-feed to produce eggs (anautogenous) whileA. atropalpus always produces a first clutch of eggs without blood-feeding (facultatively autogenous). We recently characterized the gut microbiota ofA. aegypti andA. atropalpus that were reared identically in the laboratory. Here, we assessed the effects of specific members of the gut microbiota inA. aegypti andA. atropalpus on female fitness including egg production. Methods GnotobioticA. aegypti andA. atropalpus larvae were colonized by specific members of the gut microbiota. Survival, development time, size and egg production for each treatment was then compared to axenic and conventionally reared larvae. Results Most species of bacteria we tested supported normal development and egg production byA. aegypti but only one betaproteobacterium, aComamonas, supported development and egg production byA. atropalpus to equivalent levels as conventionally reared females.Aedes atropalpus females colonized byComamonas contained similar stores of glycogen and protein as conventionally reared females, whereas females colonized byAquitalea did not. Small differences in bacterial loads were detected between gnotobiotic and conventionally rearedA. aegypti andA. atropalpus, but this variation did not correlate with the beneficial effects ofComamonas inA. atropalpus . Conclusions Specific members of the gut microbiota more strongly affected survival, size and egg production byA. atropalpus thanA. aegypti .